Long‐Life, High‐Voltage Acidic Zn–Air Batteries. Issue 5 (21st December 2015) - Li, Longjun; Manthiram, Arumugam
Abstract : An acidic Zn–air battery (AZAB) is developed as a next‐generation rechargeable metal–air battery. The use of a solid electrolyte enables alkaline Zn/Zn(OH)4 2− redox at the anode side and acidic oxygen reduction reaction (ORR)/oxygen evolution reaction (OER) at the cathode side. The developed AZAB solves the persistent problems facing conventional Zn–air batteries, such as CO2 ingression, dendrite penetration, zincate loss, and low cell voltage.